2012
DOI: 10.1007/s00430-011-0223-0
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of serum microRNA signatures as a novel biomarker for occult hepatitis B virus infection

Abstract: The implementation of hepatitis B surface antigen (HBsAg) screening tests has significantly enhanced blood transfusion safety. However, the transmission of HBsAg-negative blood components can still occur in the acute phase of infection during the seronegative window period or during chronic stages of infection such as occult hepatitis virus B infection (OBI). OBI, characterized by the presence of HBV infection without detectable HBsAg, is capable to elude the routine detection with HBV serologic markers and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
0
28
1
Order By: Relevance
“…A combination of the serum levels of miR-361-5p, miR-889 and miR-576-3p were shown to distinguish pulmonary tuberculosis patients from healthy individuals [26]. Li and colleagues found that four miRNAs, let-7c, miR-23b, miR-122 and miR-150, were differentially expressed in the sera of patients with occult hepatitis virus B infection (OBI) and showed a high level of accuracy in discriminating OBI cases from the non-infected controls [43]. To identify potential biomarkers for this novel H7N9 virus infection, we evaluated four serum miRNAs (miR-17, miR-20a, miR-106a and miR-376c) by ROC curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of the serum levels of miR-361-5p, miR-889 and miR-576-3p were shown to distinguish pulmonary tuberculosis patients from healthy individuals [26]. Li and colleagues found that four miRNAs, let-7c, miR-23b, miR-122 and miR-150, were differentially expressed in the sera of patients with occult hepatitis virus B infection (OBI) and showed a high level of accuracy in discriminating OBI cases from the non-infected controls [43]. To identify potential biomarkers for this novel H7N9 virus infection, we evaluated four serum miRNAs (miR-17, miR-20a, miR-106a and miR-376c) by ROC curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-150 might inhibit replication of H1N1 virus by targeting the PB2 gene, which is one component of ribonucleoprotein responsible for virus RNA replication and transcription [53]. Moreover, miR-150, let-7c, miR-23b and miR-122 were differentially expressed in occult hepatitis virus B infection (OBI) sera compared to healthy control sera, and thus, these four miRNAs have a potential to be biomarker for OBI detection [54].…”
Section: Other Virus Infectionsmentioning
confidence: 99%
“…New animal models for HBV transmission have been developed, such as inoculating chimeric mice with human hepatocytes by human HBV [97]. In addition, a recent study claimed great diagnostic accuracy of the differential expression of HBV microRNA profile in serum for identifying OBI [98]. However, for the vast majority of HBV infections located in the developing countries, routine serologic screening with HBsAg and anti-HBc remains the best affordable strategy for the time being and probably for at least a decade ahead.…”
Section: Discussionmentioning
confidence: 99%